Plasma proteome of buffaloes - de Pontes, Leticia Gomes [UNESP]; Cavassan, Nayara Rodrigues Vieira [UNESP]; de Barros, Luciana Curtolo [UNESP]; Ferreira Junior, Rui Seabra [UNESP]; Barraviera, Benedito [UNESP]; Santos, Lucilene Delazari dos [UNESP] (Wiley, 2017)
The proteomic approach has aroused the interest of veterinary medicine researchers, especially regarding the production of biopharmaceuticals and diagnosis of diseases in farm animals. Water buffaloes have gained prominence in the world economy due to the quality of their milk, meat, and leather, in addition to being an important donor of blood components. This work aimed to identify and characterize the proteins present in the blood plasma of Murrah buffaloes (Bubalus bubalis) through 2D electrophoresis, in gel protein digestion followed by mass spectrometry technique and for albumin depletion, in solution protein digestion followed by shotgun analysis. Our results showed the identification of 112 protein spots and 35 individual proteins, respectively. The abundant proteins were represented by albumin, fibrinogen-α, fibrinogen-β, fibrinogen-γ, immunoglobulins in general, α-1-antiproteinase, α-1B-glycoprotein, α-2-HS-glycoprotein, α-macroglobulin, apolipoprotein A1, antithrombin-III, endopin 2B, fetuin-B, retinol-binding protein, serotransferrin, transthyretin and vitamin D-binding protein. Most of these proteins are related to the signaling pathways of the complement system and coagulation cascade. The results allowed a better understanding of the protein composition of these blood components, thus promoting studies on animal health in the search for molecular markers of zoonotic diseases in buffaloes.
Keywords: 2D-electrophoresis; Bubalus bubalis; Fibrin sealant; Mass spectrometry; Plasma